القيم الثقافية والاجتماعية في الومضات الاشهارية التلفزيونية -دراسة سيميولوجية لعينة من الومضات الاشهاريةالمقدمة عبر قناة الشروق الجزائرية - - بليل فايزة; رواق ليلى; مشرف سيفون باية (جامعة محمد بوضياف -المسيلة, 2024)
تعتبر القيم الاجتماعية والثقافية حقل واسع، يصعب تحليلها وإدراك أهميتها بكونها أفكار مجردة تتجسد عن طريق سلوك الذي يؤمن بها ويتبناها سواء عن طريق الوراثة أو الاكتساب، حيث يقوم الإشهار التلفزيوني بنقل هذه الأفكار المختلفة بناءا على مجموعة من المتغيرات ومحاولة تكييفها بما يتوافق مع المجتمع الذي تنشط فيه، حاولت هذه الدراسة أن تعالج موضوع القيم الاجتماعية المبثة على قناة الشروق الجزائرية، من خلال معرفة دلالات الألوان والأشكال في الخطاب الإشهاري التلفزيوني في هاته الإشهارات موضوع الدراسة، ومعرفة مدى مساهمة إشهارات الشروق في تشكيل وتعزيز قيم المجتمع الجزائري. كما تهدف هذه الدراسة إلى تسليط الضوء على كيفية تحليل الإشهار التلفزيوني الذي يعتبر نمط إتصالي مميز وهام في إيصال المعلومات والرسائل إلى الجماهير والتأثير عليهم ثقافيا واجتماعيا، وهذا بتطبيق المنهج السيميولوجي وكنموذج للدراسة اخترنا الإشهار التلفزيوني ''طماطم عمور'' والإشهار التلفزيوني ''كسكس سويسيمي'' وكلاهما يعتمد على ربط المنتوج بالقيم الاجتماعية والثقافية من اجل إقناع المشاهد وجذب انتباهه لإقتناء المنتج. Social and cultural values are considered a broad field. It is difficult to analyze them and realize their importance, as they are abstract ideas that are embodied through the behavior of those who believe in them and adopt them, whether through inheritance or acquisition. Television advertising transmits these different ideas based on a set of variables and attempts to adapt them in accordance with the society in which it operates. In it, this study attempted to address the issue of social values broadcast on the Algerian Al-Shorouk channel, by knowing the connotations of colors and shapes in the television advertising discourse in these advertisements, the subject of the study, and knowing the extent to which Al-Shorouk advertisements contribute to shaping and strengthening the values of Algerian society. This study also aims to shed light on how to analyze television advertising, which is considered a distinctive and important communication style in conveying information and messages to the masses and influencing them culturally and socially. This is by applying the semiological approach. As a model for the study, we chose the television advertising “Amor Tomatoes” and the television advertising “Suisimi Couscous”. ''Both of them depend on linking the product to social and cultural values in order to convince the viewer and attract his attention to purchasing the product.
¡ :(Semantics, television advertising, semiology, image, advertising discourse) (الدلالة، الإشهار التلفزيوني، السيميولوجيا، الصورة، الخطاب الإشهاري)